Influential Article Review - Transitioning to an Open Network Organization - Ramsey, Sonia; Glover, Winifred; Rodgers, Priscilla (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines business and innovation. We present insights from a highly influential paper. Here are the highlights from this paper: Organizations around the world are designing new forms of organizing in order to deal with the challenges of advances in information technology and digitization that promote increases in customization and innovation in the face of global competition. This paper presents a case study examining the challenges experienced by a large multinational firm as it transforms from a hierarchical product organization to an open platform network organization. We show that (a) role confusion, (b) control imbalance, and (c) staffing mismatches are key challenges associated with organizational redesign. The main lessons drawn from this case are discussed. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.